Gendered aspirations and occupations among rural youth, in agriculture and beyond: A cross-regional perspective - Elias, Marlène; Mudege, Netsayi N.; López, Diana E.; Najjar, Dina; Kandiwa, Vongai; Luis, Joyce S.; Yila, Jummai Othniel; Tegbaru, Amare; Ibrahim, Gaya; Badstue, Lone B.; Njuguna-Mungai, Esther; Bentaibi, Abderahim (2018)
Based on 25 case studies from the global comparative study ‘GENNOVATE: Enabling gender equality in agricultural and environmental innovation’, this paper explores rural young women’s and men’s occupational aspirations and trajectories in India, Mali, Malawi, Morocco, Mexico, Nigeria, and the Philippines. We draw upon qualitative data from 50 sex-segregated focus groups with the youth to show that across the study’s regional contexts, young rural women and men predominantly aspire for formal blue and white-collar jobs. Yet, they experience an aspiration achievement gap, as the promise of their education for securing the formal employment they seek is unfulfilled, and they continue to farm in their family’s production. Whereas some young men aspired to engage in knowledge-intensive or ‘modern’ agriculture, young women did not express any such interest. Framing our analysis within a relational approach, we contend that various gender norms that discriminate against women in agriculture dissuade young women from aspiring for agriculture-related occupation. We discuss the gendered opportunity spaces of the study sites, the meanings these hold for allowing young women and men to achieve their aspirations and catalyze agricultural innovation, and implications for agricultural policies and research for development. Our findings show that youth and gender issues are inextricably intertwined and cannot be understood in isolation one from the other.